Bangledesh agriculture : performance and policies : compundium volume IV : markets and prices (Dhaka : UNDP, 1989)
Environment Management
Bibliography : p. 246-247
1995-05-13
Keywords: Agricultural management; Agricultural policy; Markets; Prices; Bangladesh